Pendidikan Humanis dalam Prespektif Islam (Implementasi Nilai-Nilai Ketauhidan dalam Pembeljaran) - M Muizzuddin (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2017)
This paper will explain about concept of humanist education on perspective of Islam, humanist education is the concept of education that departs from the assumption that humans basically have the same potential that must be developed and fostered intensively. In humanist education, between educators and learners are not subject-object positions, but learners are positioned equally (egalitarian), as educated subjects as well as educational subjects (learning together). Humanist education directly invites learners to find solutions to problems encountered with guidance from educators. Islam as a religion of compassion has revolutionized the forms of dehuma-nization in the form of hegemonic-exploitative to humans who are considered inferior in material terms. The authors conclude, with the concept of monotheism, Islam tries to position the same man before his Lord. The divine values (tauhid) are the foundation for interaction among human beings without questioning any biological or material differences. So, tauhid is the foundation of humanist education which will make a personal individual and social as God's purpose created man become ‘abd as well as the leader on earth.Keywords: Education, Humanis, Value